Pengaruh Return On Asset (ROA), Debt To Equity Ratio (DER) dan Earning Per Share (EPS) Terhadap Harga Saham Pada Perusahaan LQ45 Yang Terdaftar di BEI - Larasati Andini; Dian Ayu Andriani (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
The study aims to determine the partial and simultaneous influence of the test results (t), partially the Return On Asset (ROA) variable does not affect stock prices with a calculated t value of 0.948 < t table 2.04227 with a significance value of 0.351> 0.05, partially the Debt to Equity Ratio (DER) variable does not affect stock prices with a calculated t value of 1.750 < t table 2.04227 with a significance value of 0.091> 0.05, partially the Earning Per Share (EPS) variable affects stock prices with a calculated t value of 3.635> t table 2.04227 with a significance value of 0.001 < 0.05. it is known that the Adjusted Square value is 0.326. The results of the simultaneous test (F) in this study, with a calculated F of 6.166 > 2.93 (Ftable) and a significance value of 0.002 < 0.05, simultaneously indicate that the variables Return on Assets (ROA), Debt to Equity Ratio (DER), and Earnings Per Share (EPS) influence stock prices in LQ45 companies listed on the Indonesia Stock Exchange (IDX).